FINANCIAL IMPEDIMENTS AND WOMEN ENTREPRENEURSHIP: A THEORETICAL ANALYSIS - Abro, Paras; Akhtar Katper, Sheeraz (IJRDO - Journal of Business Management, 2016)
The purpose of this paper is to analyze the financial impediments facing by the women entrepreneurship, especially in the rural areas of Sindh province in Pakistan. It is believed that rural women in Pakistan is living under despondency, powerlessness and voiceless and they don’t get much opportunities of doing businesses though having talent as well. This research was conducted to have an overview of the present conditions for female entrepreneurs based in Sindh. It was also conducted to come up with recommendations / suggestions to address existing problems to promote entrepreneurship in Sindh. This is a descriptive paper, which will provide the guidance for the empirical research further.